1990
DOI: 10.1161/01.hyp.15.5.493
|View full text |Cite
|
Sign up to set email alerts
|

Plasma endothelin levels in hypertension and chronic renal failure.

Abstract: Endothelin-l is a novel endothelium-derived vasoconstrictive peptide. Using a highly specific and sensitive radioimmunoassay for endothelin-l, plasma levels of immunoreactive endothelin-I were measured in 32 research subjects with normal renal function (21 normal subjects and II patients with essential hypertension), 24 patients with nondialyzed chronic renal failure, and 51 patients undergoing maintenance hemodialysis. Although there was no significant difference in plasma immunoreactive endothelin-l levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
2

Year Published

1991
1991
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(132 citation statements)
references
References 18 publications
9
121
2
Order By: Relevance
“…Endothelin-1 is a locally produced vasoactive peptide released from vascular endothelial cells, plasma levels of which are often elevated in patients with hypertension, obesity, type 2 diabetes, peripheral vascular resistance as well as other disease states associated with cardiovascular disease [1][2][3][4][5][6]. In addition, endothelin-1 release may be stimulated by insulin, and may be involved in maintaining vasomotor tone at rest and during insulin stimulation [4,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelin-1 is a locally produced vasoactive peptide released from vascular endothelial cells, plasma levels of which are often elevated in patients with hypertension, obesity, type 2 diabetes, peripheral vascular resistance as well as other disease states associated with cardiovascular disease [1][2][3][4][5][6]. In addition, endothelin-1 release may be stimulated by insulin, and may be involved in maintaining vasomotor tone at rest and during insulin stimulation [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Since plasma levels of endothelin-1 are elevated in various states of insulin resistance [1][2][3][4][5][6], the aim of this study was to test the hypothesis that elevated plasma levels of endothelin-1 may prevent full perfusion of muscle, thereby limiting delivery of insulin and glucose and contributing to insulin resistance. Our approach was to examine the effect of endothelin-1 infusion (both alone and in conjunction with insulin infusion) in vivo on femoral blood flow (FBF) and muscle capillary perfusion, muscle glucose uptake, and whole-body glucose infusion rate (GIR).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kon et al (21), who used anti-ET antibodies in an ischemic kidney model intending to deactivate endogenous ET, suggested that this peptide was involved in the onset of acute renal ischemic injury. Plasma levels of ET-1 have been shown to be elevated in patients undergoing hemodialysis treat ment and in patients with acute or chronic renal failure (4,(22)(23)(24). Thus, although these studies show that ET-1 plays an important role in renal function and disease, we still have little information derived from the direct obser vation of physiological and pathophysiological states related to ET-1 in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…79 Reports on plasma endothelin in essential hypertension have been controversial, with increased levels published by some, 80,81 but not all investigators. 82,83 It has now become evident that two reasons account for this apparent controversy. First, plasma endothelin tends to be elevated when hypertension is severe, with concomitant end organ damage.…”
Section: Endothelin and Hypertension In Humansmentioning
confidence: 99%